Addressing Ethnicity in Social Care Research. (24th May 2012) - Vickers, Tom; Craig, Gary; Atkin, Karl
Abstract This article surveys recent developments in relation to the dimensions of ethnicity and ethnic disadvantage in social policy research and practice, with a focus on social care. While there has been limited increase in attention to ethnicity within general policy discussion and increasing sophistication within specialist debates, advances in theory and methodology have largely failed to penetrate the research mainstream, let alone policy or practice. This is a long‐standing problem. We advocate more focused consideration of ethnicity and ethnic disadvantage at all levels. Failure to do so creates the risk of social policy research being left behind in understanding rapid changes in ethnic minority demographics and patterns of migration, with increasing disadvantage to minorities.